A new Rhagovelia (Hemiptera: Heteroptera: Veliidae) from the Brazilian Amazon, with a key to species of the robusta group known from the country - Moreira, Felipe Ferraz Figueiredo; Barbosa, Julianna Freires (Zootaxa, 2014)
Rhagovelia zecai sp. nov., from the Brazilian Amazon, is described, illustrated, compared with similar species, and included in a key to species of the robusta group recorded from the country.